Metastasizing leiomyoma during pregnancy - Souto Morlin, Jéssica; Luiz Neto, Altivo Manoel; Mendes Melo, Anelise; Carvalho Paschoini, Marina; Ronan Marquez Ferreira de Souza, Luis; do Amaral, João Henrique; Candido Murta, Eddie Fernando; Simões Nomelini, Rosekeila (Clinical and Biomedical Research, 2023)
Uterine leiomyoma is a benign tumor of myometrial tissue which affects women of reproductive age. Its prevalence increases with age and has a peak incidence at the age of forty. The term “metastasizing leiomyoma” refers to a tumor of dense connective tissue and smooth myometrial muscle cells located outside the uterus. This group of tumors can metastasize to different organs, the lung being its main focus. We present the case report of a 33-year-old female gravida 3, para 1, abortus 1, at 11 weeks of pregnancy, with pelvic masses. The diagnosis was metastasizing leiomyoma during pregnancy.